THE BIOLOGY OF DISCONNECTION: HOW LONELINESS FUELS THE FEEDBACK LOOP OF RELAPSE IN DEPRESSION AND GAD - Martyna Susek; Amadeusz Furmanek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Loneliness and social isolation are increasingly recognized as potent social determinants of mental health. While their association with psychiatric onset is well-documented, their precise neurobiological role in the relapse of Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD) remains underexplored. This review proposes an integrative feedback loop model linking perceived social disconnection to relapse risk. Methods: A narrative synthesis of 35 longitudinal and neuroimaging studies (2002–2026) was conducted. Inclusion criteria prioritized peer-reviewed research with validated measures of loneliness, clinical diagnosis of MDD/GAD (DSM-5/ICD-11), and objective neurobiological markers (HPA activity, inflammatory signaling, or neuroplasticity). Data were synthesized into endocrine, immunological, structural, and chronobiological domains to construct a multilevel feedback loop model. Results: Evidence suggests that chronic loneliness triggers a “social signal transduction” pathway, upregulating pro-inflammatory genes and promoting glucocorticoid resistance. Neuroimaging reveals amygdala hyper-reactivity and prefrontal cortical thinning associated with perceived isolation. Sleep fragmentation and impaired glymphatic clearance further exacerbate neurobiological vulnerability, while activation of the kynurenine pathway reduces responsiveness to monoaminergic therapies. Combined with social capital depletion, these mechanisms create a self-perpetuating cycle of recurrence. Conclusions: Relapse in MDD and GAD represents a systemic failure driven by the biology of disconnection. Sustained remission requires integrating interventions that restore social connectivity alongside pharmacotherapy to disrupt the neuroinflammatory feedback loop and enhance treatment efficacy.